Equivalence of electric charge and energy - Nikolayevich Sukhanov , Vladimir (International Journal of Physical Research, 2024)
The equivalence of electric charge and energy is the principle that everything that has an electric charge has an equivalent amount of energy and vice versa. Main methods used: conversion of natural units, algebra, analogy. The equivalence of electric charge and energy, despite the wide use in describing the principles of physics and astrophysics, has not yet been formulated. In this work, the formula for the equivalence of electric charge and energy is presented. This is done on the basis of known measurement systems, parameters and principles of physics.Five examples (Stoney units, Planck units, Newton's law of universal gravitation, Coulomb's law and Ampere's law) of the algebraic notation of this principle show its universality. Five examples should justify the universality of the new principle and its use in physics, astrophysics and technology.New physical Units are proposed for mass and electric charge has been proposed, each of which is suitable for measuring both mass and electric charge. The paper gives perspectives of using the proposed equivalence: starting calculation of mass excess, refinement of orbits of celestial, and Einstein field equation.